Combined chemotherapy and irradiation in anaplastic thyroid carcinoma - Pejčić Ivica (Archive of Oncology, 2003)
Background: Anaplastic thyroid carcinoma (ATC) is a very rare and extremely aggressive cancer; patient's death usually occurs rapidly after diagnosis with a mean survival of six months in the majority of individual research series. Treatment of ATC ranges from surgery, radiotherapy, chemotherapy, or a combination of these regimes. Yet, the optimal sequence of treatment modalities has not been established. Methods: From 1997 to 2002 six consecutive patients with a histological diagnosis of ATC were treated with combined chemotherapy and irradiation at our Clinic for Oncology, Clinical Center Ni¹. Five of these patients were females and 1 male, aged between 28 and 71 years (mean age: 57 years). None of them had distant metastases at the time of diagnosis. Extrathyroidal extension was present in 3 patients with invasion into skin and hypoderm. Treatment consisted of doxorubicin 60 mg/m 2 plus cisplatin 60 mg/m 2 every three weeks. Total doses ranged between 158-375 mg/m 2 for doxorubicin and 183-380 mg/m 2 for cisplatin. External beam radiation to the neck was administered, at a daily dose of 1.2 Gy, up to total doses ranging between 45-60 Gy. Results: One patient achieved a complete response (CR) and one patient achieved a partial response (PR). Three patients had stable disease. One patient with CR progressed during follow-up and died 18 months from bone and brain metastases. The treatment was moderately well tolerated, although all patients experienced some mild form of toxicity; neutropenia occurred in all patients, but none of them required hospital admission. Median survival was 8 months (range: 4-18 months). Conclusion: We concluded that the present regimen produces meaningful responses for patients with localized ATC. A randomized study is needed to determine the effect on survival.